Antropologi Sastra Lisan Muayak di Desa Sukamarga Kecamatan BPR Ranau Tengah Kabupaten Oku Selatan - Emi Karmila; Liza Murniviyanti; Hetilaniar Hetilaniar (Departement of Mathematics Education, 2023)
Literary anthropology is a science that analyzes a literary work in relation to cultural issues. The problem of this research is how is the anthropology of literature which includes language, religion and local wisdom of Muayak's oral literature in Sukamarga Village, BPR Ranau Tengah District, OKU Selatan District. This study aims to find out and describe how literary anthropology includes language, religion and local wisdom of Muayak's oral literature in Sukamarga Village, BPR Ranau Tengah District, OKU Selatan Regency. researcher. The data in this study were Muayak's oral literary poems in Sukamarga Village, BPR Ranau Tengah District, OKU Selatan District. The method used in this research is descriptive method. Data collection techniques used in research are observation, interviews and recording. The data analysis technique used in this research is content analysis technique. Based on the results of the discussion, it can be interpreted that in the language system, namely the communication tool used by the community to convey information to their interlocutors both orally and in writing, while the language used by the community is using the regional language of Ranau. The religious system is the human belief in a higher power to communicate with God. Meanwhile, local wisdom is ancestral cultural values ​​that have long been owned and obtained through the experience of certain communities.